1977
DOI: 10.1111/j.1471-4159.1977.tb10633.x
|View full text |Cite
|
Sign up to set email alerts
|

AN ADAPTATION OF THE PUSH‐PULL CANNULA METHOD TO STUDY THE IN VIVO RELEASE OF [3H]DOPAMINE SYNTHESIZED FROM [3H]TYROSINE IN THE CAT CAUDATE NUCLEUS: EFFECTS OF VARIOUS PHYSICAL AND PHARMACOLOGICAL TREATMENTS

Abstract: Abstract— The release of [3H]dopamine ([3H]DA) continuously synthesized from l‐[3,5–3H]tyrosine from the caudate nucleus of the cat was estimated in halothane anaesthetized or‘encéphale isolé’animals. For this purpose, an improved superfusion cannula, avoiding tissue damage, was used. The best localization for the tip of the superfusion cannula was found first by determining the topographical distribution of endogenous DA within the caudate nucleus. A rostro‐caudal heterogenous distribution of the transmitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…A smaller cannula and lower flow rates such as those used here, however, have been shown to cause only limited tissue damage (Yaksh and Yamamura, 1974) and negligible unspecific transmitter release from damaged cells (Bartholini et al, 1976). Tissue damage may also be reduced by using an open pulling system, such as a siphon (Nieoullon et al, 1977). NA and DA are known to be oxidized rapidly in oxygenated physiological saline at 37°C (Hughes and Smith, 1978;Philips and Robson, unpublished observations).…”
Section: Resultsmentioning
confidence: 82%
“…A smaller cannula and lower flow rates such as those used here, however, have been shown to cause only limited tissue damage (Yaksh and Yamamura, 1974) and negligible unspecific transmitter release from damaged cells (Bartholini et al, 1976). Tissue damage may also be reduced by using an open pulling system, such as a siphon (Nieoullon et al, 1977). NA and DA are known to be oxidized rapidly in oxygenated physiological saline at 37°C (Hughes and Smith, 1978;Philips and Robson, unpublished observations).…”
Section: Resultsmentioning
confidence: 82%
“…The somata and dendrites of dopaminergic neurons in the substantia nigra and the ventral tegmental area also release dopamine (Björklund and Lindvall, 1975; Geffen et al, 1976; Cheramy et al, 1981; Jaffe et al, 1998), as first shown by H 3 -incubated nigral slices (Geffen et al, 1976), and by push-pull cannula in vivo in anaesthetized rats (Nieoullon et al, 1977). More recently, extracellular dopamine increases were detected upon electrical stimulation by use of fast scan cyclic voltammetry in slices containing the substantia nigra or the ventral tegmental area (Rice et al, 1997; Chen and Rice, 2001; Chen et al, 2006; Ford et al, 2010), suggesting that dopamine had been released from the somata and dendrites, presumably through exocytosis (Fortin et al, 2006; Witkovsky et al, 2009).…”
Section: Dopaminementioning
confidence: 96%
“…This led us to study the effects on the activity of the nigrostriatal dopami nergic neurons of stimulation of a cerebral cortical area and of a cerebel lar nucleus. Changes in the activity of these neurons were assessed by measuring the release of dopamine (DA) from terminals in the caudate nuclei [3] and from dendrites in the substantiae nigrae [4] in halothaneanesthetized cats. For this purpose, push-pull cannulae were simultane ously introduced in the four structures and the released 3H-DA was deter mined in superfusates during the continuous delivery of L-3,5-3H-tyrosine, as previously described [3,4], Symmetric responses were obtained during repeated unilateral electri cal stimulation of the cerebral motor cortex for 10 min.…”
mentioning
confidence: 99%